DETERMINAN KEPATUHAN WAJIB PAJAK HOTEL DAN RESTORAN DI JAKARTA BARAT - Vanessa Gabriella; Haryo Suparmun (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Hotel and restaurant tax are part of the local taxes that are regulated by each region. Those are also local revenue for the region. This study aims to obtain the effect of distributive justice, service quality, enforcement of tax sanctions, moral obligations, awareness of paying taxes, taxation knowledge, and the effectiveness of the tax system on hotel and restaurant taxpayers compliance in West Jakarta. The object of this study are hotel and restaurant taxpayers located in the West Jakarta. The convenience sampling method are used and 67 respondents passed the respondent criteria from the responses of distributing questionnaires in the West Jakarta area. The results indicate that service quality, taxation knowledge, and effectiveness of the tax system have significant influence on hotel and restaurant taxpayer compliance in West Jakarta. While distributive justice, enforcement of tax sanctions, moral obligations, and awareness of paying taxes do not have effect on hotel and restaurant taxpayer compliance in West Jakarta.